Appropriate Use Of Anti-Diabetic Medicine In Diabetes Mellitus Patients In BPJS Participants In The Outstanding Policy Of Dr H.Soewondo Kendal 2020 - Ika Pratiwi; Elvira Rosa; Nurul Syazwani; Agustina Katikasari (CV. AFDIFAL MAJU BERKAH, 2024)
Diabetes Mellitus (DM) is a chronic condition that occurs because the body cannot produce insulin normally or insulin cannot work effectively. Indonesia is ranked fourth in the number of people with DM in the world after the United States, India and China. Rational use of drugs requires that patients receive treatment according to clinical needs, in the required dose of each individual within a certain period of time at the lowest cost. This research is a descriptive research. Descriptive research method is a research method that is carried out with the main aim of making a picture or description of a situation objectively. Descriptive research methods are used to solve or answer the problems being faced in the current situation. The profile of the use of antidiabetic drugs in terms of gender is mostly women with a percentage of 57.7%, most patients are in the 40-60 year age group as much as 50.0%. The most use of single antidiabetic drugs is sulfonylurea 33.6%, combination therapy mostly uses 3 classes of drugs by 63.6%, namely Alpha Glucoside Inhibitors, Sulfonylureas and Biguanides. For the administration of combination therapy, the most insulin is a combination of longrapid and85.7 actingacting %.